Cultural hybridization in the production of self-published comics by Malay fan artists of Japanese popular culture - Junid, Iman (2016)
The development of Malaysian comic industry can be witnessed throughout the years from the changes it has undergone and the availability of its varieties in the local market. A new market of the creative art has also emerged from fan conventions in Malaysia, where fans of Japanese popular culture participated to showcase and sell their (re)produced works including self-published comics. Few past studies have highlighted the presence of manga (Japanese comic) stylization in recent Malaysian comics. However, only one study has provided empirical evidence for such claim in the comics by one Malaysian Chinese artist, indicating cultural hybridity between manga and Malaysian comics. Such attribution in the comic production by other ethnicities is still unexplored. To further understand cultural hybridization in the production of selfpublished comics from the view of Malay fan artists of Japanese popular culture, a qualitative study was designed. For the data generation, in-depth interviews were conducted with ten Malay comic artists who were actively producing self-published original comics and engaged in Malaysian fan conventions. The interviews were transcribed verbatim and analyzed by employing thematic analysis. In addition, the comics of the selected artists were also acquired as the supporting data for the analysis. From the analysis, three main themes were developed, namely "Attribution to the Japanese Popular Culture", "Representations of Locality", and "Towards Transnationality". Firstly, the artists' comic production were found to be attributed to the Japanese popular culture. Their interests in drawing and producing comics were first initiated by their consumption of Japanese popular culture. They continued to develop their skills and got engaged in selling comics in Malaysian fan conventions through prosumption (simultaneous production and consumption). For the second theme, two ways of representations of locality were found in the artists' comics, namely realistic and fantastical representation. By these representations, the artists intended to portray the localities based on real life experiences or issues. For the final theme, the artists showed a progress towards transnational identification by three circumstances. They negotiated with the locals’ criticisms to adapt to the local moralities and publication guidelines. Moreover, due to technical difficulties or conflict with personal interests or principles, they have created elements that are situated in-between of its respective references. They also expressed their preference for individual identification over national identification on the originality of their comics. The study concluded that cultural hybridization in the production of self-published comics by the Malay fan artists of Japanese popular culture is a development of transnational identification. Despite the artists were first initiated to draw by their consumption of Japanese popular culture, they did not intend to portray such attribution in their comics but portrayed the localities instead. The mixed references in their comics indicate displacement of fixed nationalities, leading to the artists' sense of originality belongs to neither their references' origins nor their own nation. Cultural hybridization in their comic production occurs not only at the global level among the nations, but also at the very individual level which could lead to more diversified cultural interpretations and understandings.